Modeling water mass formation in the Mertz Glacier Polynya and Adelie Depression, East Antarctica - Marsland, SJ; Nathaniel Bindoff; Guy Williams; Budd, WF (2004)
High rates of sea ice growth rejection in the Mertz Glacier Polynya drive the production of dense continental shelf waters in the Adélie Depression. We consider the rate of outflow of waters having sufficient density to sink into the neighboring abyssal ocean and form Adélie Land Bottom Water (ALBW). Along with Weddell and Ross Sea Bottom Waters, the ALBW is an important source of Antarctic Bottom Water. The relevant processes are modeled using a variant of the Max Planck Institute Ocean Model (MPIOM) under daily NCEP-NCAR reanalysis forcing for the period 1991-2000. The orthogonal curvilinear horizontal grid allows for the construction of a global domain with high resolution in our region of interest. The modeled Mertz Glacier Polynya is realistic in location and extent, exhibiting low ice thickness (<0.4 m) and low ice fraction (<50%). The net surface ocean to atmosphere heat flux exceeds 200 W m2 and is dominated by sensible heat exchange. In wintertime (May through September inclusive), 7.5 m of sea ice forms over the Adélie Depression at a rate of 4.9 cm d-1: this results in annual average volumetric production of 99 km3 of sea ice. The associated brine release drives dense shelf water formation. The off-shelf flow of dense water exhibits strong interannual variability in response to variability in both atmospheric forcing and ocean preconditioning. Averaged over the period 1991-2000 the off shelf flow of dense water is 0.15 Sv: for a period of strong outflow (1993-1997), this increases to 0.24 Sv. Most of the outflow occurs during July through October, at a rate of 0.40 (0.63) Sv over the period 1991- 2000 (1993-1997). The peak mean monthly outflow can exceed 1 Sv. Copyright 2004 by the American Geophysical Union.